PENGARUH FLEKSIBILITAS MANUFAKTUR PADA KINERJA (Studi Komparasi pada Perusahaan Batik dan Mebel di Surakarta) - SARWOTO SARWOTO (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
This research comparation relationship manufacturing flexibility with firm performance between batik industries and furniture industries. The data was collected through a survey using a questionnaire with convinience sampling to 50 batik firms and 50 furniture firms in Solo - Indonesia. Response rate of 98 % for furniture fims and 100% for batik firms. This study applies partial least square to investigate the research model. The results showed that have different between effect of competences of manufacturing flexibility on capabilities of manufacturing flexibility in batik and mebel industries context. Capabilities of manufacturing flexibility measured by volume flexibility and mix flexibility. In batik industry context,  have significant effect of competences of manufacturing flexibility on volume flexibility and mix flexibility. While in furniture industry context, competences of manufacturing flexibility have significant effect on volume flexibility but no significant effect on mix flexibility. Relationship between capabilities of manufacturing flexibility and firm performance, both batik and furniture industries showed no significant relationship. Further research should be conducted on a large sample. Research can be conducted in wider area coverage so that results can be used for generalization. Further study also required added another independent variable to predict firm performance.